Thermodynamics Study of Lac Dyeing of Silk Yarn Coated with Chitosan - CHAIRAT, Montra (Walailak Journal of Science and Technology (WJST), 2011)
A thermodynamic study of lac dyeing of silk pretreated with chitosan at pH 3.0 was investigated in a batch system. It was found that the adsorption of lac dye on silk pretreated with chitosan could be described by the Langmuir isotherm. The results showed that the pretreatment of silk with chitosan provided an enhancement of dye uptake on silk and also decreased the dye desorption from silk yarn compared with the results in the absence of chitosan. The negative value of the enthalpy change (DHº) for the adsorption of lac dye on silk pretreated with chitosan indicated that the adsorption process was an exothermic one.